Inclusive Marketing Strategy as an Instrument for Empowering Marginalized Groups in Economic and Social Development - Al Hakim, Yusuf Rahman; Sigita, Dwi Sembe; Irfan, Mochamad (Bulletin of Science, Technology and Society, 2025)
This article examines the contribution of marketing practices in reinforcing social inclusion and the empowerment of marginalized groups by analyzing the economic and social dimensions of inclusive marketing strategies. The primary focus is directed toward understanding how marketing can serve as a strategic instrument to enhance the participation of marginalized groups through market access, social representation, and the strengthening of economic capacities. The strategies analyzed encompass co-creation, alternative distribution, pricing innovation, and the utilization of digitalization as a marketing medium that expands market access. The findings of the study indicate that marketing functions as an empowerment mechanism when it is designed with a participatory and community-based orientation. The involvement of marginalized groups in chain broadens value their economic bargaining power, while simultaneously strengthening the social legitimacy of enterprises. Moreover, marketing strategies that integrate inclusive narratives in brand communication are capable of reducing social stigma and fostering a sense of ownership within the community. Community-based marketing approaches have been shown to establish collaborative networks that enhance collective capacity and drive economic participation. Overall, inclusively designed marketing plays a significant role in creating a more just and balanced business ecosystem. This article underscores the importance of integrating marketing strategies with social agendas to achieve sustainable development. Thus, marketing should not be viewed solely as a business function but also as a social instrument that contributes to the welfare of marginalized groups